APPLYING TOTAL PHYSICAL RESPONSE TROUGH SNAKE AND LADDER GAME FOR TEACHING ENGLISH FOR CHILDREN TO KINDERGARTEN TEACHERS IN SOUTH SEMARANG - Ratno Ratno (Jurnal Lingua Idea, 2015)
This research was conducted to describe the applying Total Physical Response through snake and ladder game for teaching English for children to kindergarten teachers in South Semarang District in academic year of 2014/2015 and to find out the result of applying Total Physical Response through game for teaching English for children. The data source of my study was the teachers of kindergarten in south Semarang District in academic year of 2014/2015 which consists of 30 kindergarten teachers. The instruments consist of vocabulary and free simple writing test. It means that the kindergarten teachers were taught first about vocabulary for kindergarten children and then they were asked to make simple writing sentence related to vocabularies have been learned. The learning process was based on Total Physical Response through snake and ladder game. This study is an action research. There were four steps in conducting an action research: Planning. Acting, Observing, and Reflecting. This action research was done in two cycles. The teaching of vocabulary and simple sentence through snake and ladder game contributes significantly to the achievement of kindergarten teachers’ improvement. Based on the result of the pre cycle, there were 30% participant who passed the indicator standard. After applying Total Physical Response through snake and ladder game on first cycle, there were 50% participants who passed indicator standard and on the second cycle, there were 86 % of improvements of mastering vocabulary and simple writing sentences. Based on this result, I could draw conclusion that applying Total Physical Response through snake and ladder game can improve the kindergarten teachers’ vocabulary and simple writing skill.